Merger policy for a dynamic and digital Canadian economy - Keldon Bester (Centre for International Governance Innovation (CIGI), 2022)
As an element of competition and antitrust law frameworks, merger policy plays an important role in preventing acquisitions that would otherwise allow incumbent firms to extinguish competitive threats and entrench their dominance. But evidence suggests that current approaches to merger law in Canada and abroad have underestimated the harms these transactions can pose to competition and overestimated the effectiveness of the remedies intended to mitigate those harms. Although relevant across the Canadian economy, this permissive treatment of mergers is particularly pronounced in digital markets, where platform business models, the importance of potential competitors and the role of intangible assets such as data as a barrier to entry test the assumptions underlying the country's merger law. Canada's current law and jurisprudence mean the Competition Bureau, Canada's sole competition authority, is limited in its ability to detect potentially harmful transactions, faces material barriers to intervening and fully remedying the harms of those transactions, and is unable to assess the outcome of previous action or inaction. This paper provides recommendations for Canada to ensure its merger law is calibrated for a modern economy.
Keywords: 330